Uterine Artery Doppler in Screening for Preeclampsia and Fetal Growth Restriction - Marianna Amaral Pedroso; Kirsten Rebecca Palmer; Ryan James Hodges; Fabricio da Silva Costa; Daniel Lorber Rolnik (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To perform a comprehensive review of the current evidence on the role of uterine artery Doppler, isolated or in combination with other markers, in screening for preeclampsia (PE) and fetal growth restriction (FGR) in the general population. The review included recently published large cohort studies and randomized trials. Methods A search of the literature was conducted usingMedline, PubMed, MeSH and ScienceDirect. Combinations of the search terms "preeclampsia," "screening," "prediction," "Doppler," "Doppler velocimetry," "fetal growth restriction," "small for gestational age" and "uterine artery" were used. Articles in English (excluding reviews) reporting the use of uterine artery Doppler in screening for PE and FGR were included. Results Thirty articles were included. As a single predictor, uterine artery Doppler detects less than 50% of the cases of PE and no more than 40% of the pregnancies affected by FGR. Logistic regression-based models that allow calculation of individual risk based on the combination of multiple markers, in turn, is able to detect ~ 75% of the cases of preterm PE and 55% of the pregnancies resulting in small for gestational age infants. Conclusion The use of uterine artery Doppler as a single predictive test for PE and FGR has poor accuracy. However, its combined use in predictive models is promising, being more accurate in detecting preterm PE than FGR.